Role Of Guduchi (Tinospora Cordifolia ) In Covid-19– A Review: Life Sciences-Pharmaceutics - Misar Wajpey, Sadhana; U. Nimbhorkar, Ashish (International Journal of Life Science and Pharma Research, 2023)
The cause of COVID-19 disease is the newly found corona virus which can transmit from animals to humans. The epidemic commenced in Wuhan city of China in December 2019. It manifests as pyrexia, fatigue, and cough. Symptoms like headache, running nose, congestion, sore throat, and shortness of breath are also seen in several individuals. Currently, no definite medicines are available to prevent and manage Corona disease. Prevention is the only measure to fight against Corona. Ayurveda is the best option having many preventive as well as curative measures. For disease prevention, Rasayanachikitsa (Rejuvenating therapy) is described in Ayurveda, which helps in boosting immunity. This review aims to focus on the immunomodulatory properties of Guduchi and its benefits in the prevention and management of COVID-19 diseases. Related literature and research articles were searched and reviewed thoroughly. Many herbal drugs having Rasayana properties are described in Ayurveda, which help in activating immune system. Immunity is the body’s defense mechanism that protects an individual from invading microorganisms and thus prevents disorders caused by them.Guduchi(Tinispora cordifolia) is one of the Rasayanaherbal drugs which can be used in COVID-19. Many research studies conducted onGuduchiproveditsimmunomodulatory, antioxidant, antimicrobial, antiviral, anti-inflammatory, and antipyretic properties. Hence this review is conducted to study the role ofGuduchi in prevention and relieving symptoms of COVID-19. Research studies should be conducted to prove its efficacy and exact mechanism in Coronavirus disease.